2020
DOI: 10.14336/ad.2020.0711
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on Mesenchymal Stem Cells (MSCs), Adipose-Derived Mesenchymal Stem Cells (AD-MSCs), Drugs, and Vaccines in Inhibiting COVID-19 Disease

Abstract: Mesenchymal Stem Cells (MSCs), and Adipose-Derived Mesenchymal Stem Cells (AD-MSCs) have been used for many years in regenerative medicine for clinical and surgical applications. Additionally, recent studies reported improved respiratory activity after intravenous administration of MSCs into patients affected by coronavirus disease 2019 (COVID-19) caused by the Coronavirus 2 (SARS-CoV-2) suggesting their role as anti-viral therapy. Severe COVID-19 patients usually progress to acute respiratory distress syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 27 publications
0
44
0
Order By: Relevance
“…BM-MSCs, adipose-derived mesenchymal stem cells (AD-MSCs), and stromal vascular fraction cells (SVFs) have the ability to promote wound healing and soft tissue defects when used alone [ 29 31 ] or in combination with platelet rich plasma (PRP) and fat graft [ 32 – 34 ]. Additionally, the most recent studies reported systemically administered MSCs improve respiratory activity in patients with coronavirus disease 2019 (COVID-19) [ 35 37 ]. However, we still lack treatment guidelines given the limited evidence from comparative research, which is becoming a crucial issue hindering the clinical application of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…BM-MSCs, adipose-derived mesenchymal stem cells (AD-MSCs), and stromal vascular fraction cells (SVFs) have the ability to promote wound healing and soft tissue defects when used alone [ 29 31 ] or in combination with platelet rich plasma (PRP) and fat graft [ 32 – 34 ]. Additionally, the most recent studies reported systemically administered MSCs improve respiratory activity in patients with coronavirus disease 2019 (COVID-19) [ 35 37 ]. However, we still lack treatment guidelines given the limited evidence from comparative research, which is becoming a crucial issue hindering the clinical application of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment with mesenchymal stem cells (MSCs) has been the research hotspot of ARDS immunotherapy in recent years [ 221 ]. MSCs exert anti-inflammatory protective effects on host tissues through the potential anti-inflammatory paracrine factors IL-1ra, TNF-α-stimulated gene 6 protein (TSG-6), insulin-like-growth factor 1 (IGF-1), and prostaglandin E2 (PEG 2) pathway [ 222 ].…”
Section: Current Therapeutics and Drug Developmentmentioning
confidence: 99%
“…Administration of MSCs in COVID-19 patients seems to be a promising tool in the treatment by reducing hyperinflammation ( Gentile et al, 2020 ). MSCs from COVID-19 patients of different disease severity should be isolated and analyzed.…”
Section: Discussionmentioning
confidence: 99%